Respuesta :
Answer:
(a)
Step-by-step explanation:
Given the 2 equations
6x + 2y = - 6 → (1)
3x - 4y = - 18 → (2)
Multiplying (1) by 2 and adding to (2) will eliminate the term in y
12x + 4y = - 12 → (3)
Add (2) and (3) term by term
15x = - 30 ( divide both sides by 15 )
x = - 2
Substitute x = - 2 into either (1) or (2) and solve for y
Substituting into (1)
6(- 2) + 2y = - 6
- 12 + 2y = - 6 ( add 12 to both sides )
2y = 6 (divide both sides by 2 )
y = 3
Solution is (- 2, 3)
To determine the system with the same solution.
Substitute the x and y values of the solution into the left side of the equations and if equal to the right side then they are a solution.
(a)
8(- 2) + 4(3) = - 16 + 12 = - 4 = right side
17(- 2) + 2(3) = - 34 + 6 = - 28 = right side
Thus system (a) has the same solution